A Combined Ion Implantation/Nanosecond Laser Irradiation Approach towards Si Nanostructures Doping. (22nd February 2012) - Ruffino, F.; Romano, L.; Carria, E.; Miritello, M.; Grimaldi, M. G.; Privitera, V.; Marabelli, F.
Abstract : The exploitation of Si nanostructures for electronic and optoelectronic devices depends on their electronic doping. We investigate a methodology for As doping of Si nanostructures taking advantages of ion beam implantation and nanosecond laser irradiation melting dynamics. We illustrate the behaviour of As when it is confined, by the implantation technique, in a SiO2 /Si/SiO2 multilayer and its spatial redistribution after annealing processes. As accumulation at the Si/SiO2 interfaces was observed by Rutherford backscattering spectrometry in agreement with a model that assumes a traps distribution in the Si in the first 2-3 nm above the SiO2 /Si interfaces. A concentration of 10 14 traps/cm 2 has been evaluated. This result opens perspectives for As doping of Si nanoclusters embedded in SiO2 since a Si nanocluster of radius 1 nm embedded in SiO2 should trap 13 As atoms at the interface. In order to promote the As incorporation in the nanoclusters for an effective doping, an approach based on ion implantation and nanosecond laser irradiation was investigated. Si nanoclusters were produced in SiO2 layer. After As ion implantation and nanosecond laser irradiation, spectroscopic ellipsometry measurements show nanoclusters optical properties consistent with their effective doping.